How racial diversity and gender diversity in job positions affect the economy? - Zheng Li (Contemporary Economics, 2023)
Gender and racial discrimination at work have gradually gained more attention from the public in the recent years. With social movements such as #MeToo and #BlackLivesMatter, people start to reach the consensus that there should be more equality in society; more perspectives from different genders and different races are beneficial to society. This paper focuses on employment in the general workforce and studies how race and gender diversity in different job positions affect the economy. This paper explores to empirically explain why race and gender diversity in the workforce can have an impact on the economy. Using data from the U.S. Equal Employment Opportunity Commission and from the Federal Reserve for the years of 1996 - 2018, this paper finds that race and gender diversity at work are positively associated with the economy. Also, this dataset supports the conjecture that race and gender diversity increases total employment, which further increases the economy. This dataset also supports the possibility that race and gender diversity may increase the capacity of different perspectives, which further increases the economy. Moreover, race and gender diversity both increased during these years: from 11.783% to 23.339% and from 31.683% to 38.735% in the executive and managerial positions. This study has significant contributions to current research and practice.
Keywords: J15; J16; 330; demographic economics; racial diversity; gender diversity; total employment; GDP